COMFORTABLE URBAN ENVIRONMENT: TRENDS AND PROBLEMS OF THE ORGANIZATION - O. Petrina; M. Stadolin (Вестник университета)
At present, the formation of a modern comfortable urban environment in Russian cities acquires a special socio-economic significance. It is one of the priority state large-scale programs. The development of fundamentally new approaches to the organization of an integrated improvement of urban areas on the basis of broad participation of the population in projects for the arrangement of courtyard territories and public spaces is envisaged. It leads to a number of organizational and information problems connected with interaction with territorial authorities of the public and municipal administration. That problems are considered in the article.